Diversity and antimicrobial potential in sea anemone and holothurian microbiomes - León-Palmero, Elizabeth; Joglar, Vanessa; Álvarez, Pedro A.; Martín-Platero, Antonio; Llamas, Inmaculada; Reche, Isabel (PLOS ONE, 2018)
Marine invertebrates, as holobionts, contain symbiotic bacteria that coevolve and develop antimicrobial substances. These symbiotic bacteria are an underexplored source of new bioactive molecules to face the emerging antibiotic resistance in pathogens. Here, we explored the antimicrobial activity of bacteria retrieved from the microbiota of two sea anemones (Anemonia sulcata, Actinia equina) and two holothurians (Holothuria tubulosa, Holothuria forskali). We tested the antimicrobial activity of the isolated bacteria against pathogens with interest for human health, agriculture and aquaculture. We isolated 27 strains with antibacterial activity and 12 of these isolates also showed antifungal activity. We taxonomically identified these strains being Bacillus and Vibrio species the most representative producers of antimicrobial substances. Microbiome species composition of the two sea anemones was similar between them but differed substantially of seawater bacteria. In contrast, microbiome species composition of the two holothurian species was different between them and in comparison with the bacteria in holothurian feces and seawater. In all the holobiont microbiomes Bacteroidetes was the predominant phylum. For each microbiome, we determined diversity and the rank-abundance dominance using five fitted models (null, pre-emption, log-Normal, Zipf and Zipf-Mandelbrot). The models with less evenness (i.e. Zipf and Zipf-Mandelblot) showed the best fits in all the microbiomes. Finally, we tracked (using the V4 hypervariable region of 16S rRNA gene) the relative abundance of these 27 isolates with antibacterial activity in the total pool of sequences obtained for the microbiome of each holobiont. Coincidences, although with extremely low frequencies, were detected only in the microbiome of H. forskali. This fact suggests that these isolated bacteria belong to the long tail of rare symbiotic bacteria. Therefore, more and more sophisticated culture techniques are necessary to explore this apparently vast pool of rare symbiontic bacteria and to determine their biotechnological potentiality.